Fractal Analysis of Organic Matter Nanopore Structure in Tectonically Deformed Shales - Mingliang Liang; Min Dong; Zongxiu Wang; Kaixun Zhang; Xiaoshi Li; Xingqiang Feng (Fractal and Fractional)
Fractal analysis was used to characterize the organic matter nanopore structure in tectonically deformed shales, providing insights into the heterogeneity and complexity of the pore network. Shale samples from different tectonic deformation styles (undeformed, brittle deformed, and ductile deformed) in the Lower Cambrian Niutitang Formation in western Hunan, South China, were collected. By comprehensively applying techniques such as low-temperature gaseous (CO2 and N2) adsorption (LTGA), scanning electron microscopy (SEM), and ImageJ analysis, we accurately obtained key parameters of the pore structure. The results show ductile deformation reduces fractal dimension (DM) by ~0.2 compared to brittle deformed shale, reflecting the homogenization of organic nanopore structures. Brittle deformation leads to a more complex pore network, while ductile deformation reduces the complexity of the organic nanopore structure. The fractal dimensions are affected by various factors, with micropore development being crucial for undeformed shale, clay and pore length–width ratio dominating in brittle deformed shale, and all-scale pores being key for ductile deformed shale. This study provides the first comparative analysis of fractal dimensions across undeformed, brittle deformed, and ductile deformed shales, revealing distinct pore structure modifications linked to deformation styles. These findings not only enhance our understanding of the influence mechanism of tectonic deformation on shale pore structure and fractal characteristics but also provide a theoretical basis for optimizing shale gas exploration and production strategies. These findings offer a framework for predicting gas storage and flow dynamics in tectonically complex shale reservoirs. For instance, in areas with different tectonic deformation styles, we can better evaluate the gas storage capacity and production potential of shale reservoirs according to the obtained fractal characteristics, which is of great significance for efficient shale gas development.